Nanofiber veil applied in toughness enhancement of thermoplastic carbon fiber composites. (April 2023) - Shi, Mingjun; Takahashi, Shinya; Takeno, Akiyoshi; Nakai, Asami
This study presents an experimental investigation on thermoplastic carbon fiber composite based on PMMA resin interleaved with Polyamide electrospun nanofiber veils. In particular, the effect of improving the interfacial adhesion of the resin to nanofiber and carbon fiber on the fracture behavior of the laminates and the corresponding fracture mechanism was studied by using different molar concentrations of functional monomer hydroxyethyl acrylamide (HEAA) for copolymerization with methyl methacrylate. The effectiveness of the nanoreinforce has been addressed by Mode-Ⅰ and Mode-Ⅱ tests. The results showed that the fracture toughness of Mode-Ⅰ decreased firstly and then increased with an increase in HEAA feed with 0–5 mol% due to the change of crack tip path accompanied by the bridging mechanism shifting, the best performance was founded in 5 mol% HEAA-copolymerized thermoplastic carbon fiber composites (CFRTP) samples (17.6% for initiation and 28% for propagation); whereas a characteristic of increasing firstly and then decreasing performed under Mode-Ⅱ loading due to the formation of multilayer microcrack in nano-toughing matrix layer, the 3 mol% HEAA-copolymerized CFRTP samples exhibited good improvement (137% for initiation and 147% for propagation).